Management Fisioterapi pasca Rekonstruksi Anterior Cruciate Ligament Dextra di RSD K.R.M.T Wongsonegoro Semarang: Studi Kasus - Badzlina, Farah Afifah; Susilo, Taufik Eko; Mardianto, Halim (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: ACL injuries are common in sports like futsal and soccer, with 45% and 68% occurring due to non-contact injuries. Grade 2 and 3 injuries often result from tears. Post-reconstruction, physiotherapy is necessary to allow the patient to return to activities. There are five phases after ACL reconstruction. Case Presentation: A 20-year-old male patient was diagnosed with a total right ACL tear and experienced pain and limited range of motion. Therapy is conducted twice a week, with the patient entering phase 2. Physiotherapy interventions include strengthening exercises, squats, lunges, and one leg stance on various surfaces. Management and Outcome: Therapy is carried out 2 times every week and while the intervention is being given, the patient has started to enter phase 2. Physiotherapy interventions are given, such as Strengthening exercise, a combination of squats, lunges, and one leg stance on a mini mat, on a trampoline, and on a ballance ball reversed. Evaluations include muscle strength, joint range of motion, and functional ability using the Tegner Lysholm knee scoring scale. Discussion: Strengthening exercises are given before entering the next phase, and cryotherapy may aid tissue recovery. After four physiotherapy interventions, the patient experienced an increase in LGS, extra knee muscle strength, and functional ability. Conclusion: The post anterior cruciate ligament reconstruction phase 2 patients underwent four physiotherapy interventions, resulting in an increase in LGS, dextra knee muscle strength, and functional knee functional ability.